Effacer la frontière : nouvelles pratiques urbaines et sociales dans la vieille ville méridionale de Nicosie, Chypre - Yannis Carmenos; Marion Sabrié (L'Espace Politique)
Despite everlasting intergovernmental negotiations since 2003 and the will of the Cypriots, Greek and Turkish, to reunify Cyprus, talks have yet to end in 2017. The island is still divided and Nicosia is still not the capital of a unified State. However, bicommunal initiatives are increasing and the overrun of the conflict seems to work its way through the actions of the civil society. Nevertheless, officially and in the minds of the people, the situation has not totally improved: a certain animosity can still be felt. In practice, the border area in the South of the old city of Nicosia is reinvested and revived by its inhabitants, as well as by tourists, whose venue has accelerated since the opening of border posts in 2003. Urban transformation of the wastelands and renovations of derelict buildings are in progress. The southern part of old city has become an innovative urban laboratory, thanks to its proximity with the border. The southern part of the old city is on one hand undergoing a very tense geopolitical context, but on the other, it is reinventing itself through local actions made on the urban terrain by various institutional actors to try to rub out the border. The old town of South Nicosia slowly becomes an urban laboratory thanks to its proximity to the border.